Acinetobacter baumannii Outer Membrane Protein A Induces Pulmonary Epithelial Barrier Dysfunction and Bacterial Translocation Through The TLR2/IQGAP1 Axis - Zhang, Wang; Zhou, Hua; Jiang, Yan; He, Jintao; Yao, Yue; Wang, Jianfeng; Liu, Xiaochen; Leptihn, Sebastian; Hua, Xiaoting; Yu, Yunsong (Frontiers in Immunology, 2022)
Pulmonary epithelial barrier dysfunction is a critical pathophysiological process in pneumonia and associated invasive infections, such as those caused by Acinetobacter baumannii. However, the mechanisms underlying A. baumannii-induced pulmonary epithelial barrier dysfunction and bacterial translocation remain unclear. In this study, lungs of mice and A549 human epithelial cell monolayers were challenged with the A. baumannii wild-type strain and an outer membrane protein A (ompA) deletion strain. In addition, epithelial cells in culture were treated with purified OmpA protein or transfected with an eukaryotic expression vector encoding ompA (pCMV-ompA). Bacterial translocation across cell monolayers and intrapulmonary dissemination were measured, barrier function was evaluated in vivo and in vitro; cell migration ability was determined. The specific inhibitors C29 and JSH-23 were used to suppress the activity of Toll-like receptor 2 (TLR2) and of NF-κB, respectively. IQ-GTPase-activating protein 1 (IQGAP1) small interfering RNA was used to knock down endogenous IQGAP1 expression. In this work, we show that OmpA from A. baumannii increased the production of pro-inflammatory cytokines, remodeled the cytoskeleton, and internalized intercellular adherens junctions (AJs); these changes eventually induced pulmonary epithelial barrier dysfunction to promote bacterial translocation. IQGAP1-targeting small interfering RNA and chemical inhibition of TLR2 or NF-κB prevented high permeability of the pulmonary epithelial barrier. TLR2/NF-κB signaling was involved in OmpA-induced inflammation, IQGAP1-mediated OmpA-induced opening of the pulmonary epithelial barrier via cytoskeleton dynamic remodeling, and cellular redistribution of the major AJ protein, E-cadherin. These observations indicate that A. baumannii uses OmpA to overcome epithelial defences and cross the pulmonary epithelial barrier.